Co-Immunization With CHIKV VLP and DNA Vaccines Induces a Promising Humoral Response in Mice - Zhao, Zhimin; Deng, Yao; Niu, Peihua; Song, Jingdong; Wang, Wen; Du, Yongping; Huang, Baoying; Wang, Wenling; Zhang, Leiliang; Zhao, Ping; Tan, Wenjie (Frontiers in Immunology, 2021)
Chikungunya fever is an acute infectious disease that is mediated by the mosquito-transmitted chikungunya virus (CHIKV), for which no licensed vaccines are currently available. Here, we explored several immunization protocols and investigated their immunity and protective effects in mice, with DNA- and virus-like particle (VLP)- vaccines, both alone and in combination. Both DNA and VLP vaccine candidates were developed and characterized, which express CHIKV structural genes (C-E3-E2-6K-E1). Mice were immunized twice, with different protocols, followed by immunological detection and CHIKV Ross challenge. The highest antigen-specific IgG and neutralizing activity were induced by DNA and VLP co-immunization, while the highest cellular immunity was induced by DNA vaccination alone. Although all vaccine groups could protect mice from lethal CHIKV challenge, demonstrated as reduced viral load in various tissues, without weight loss, mice co-immunized with DNA and VLP exhibited the mildest histopathological changes and lowest International Harmonization of Nomenclature and Diagnostic Criteria (INHAND) scores, in comparison to mice with either DNA or VLP vaccination alone. We concluded that co-immunization with DNA and VLP is a promising strategy to enhance protective immunity against CHIKV infection.